Obesity Determines the Immunophenotypic Profile and Functional Characteristics of Human Mesenchymal Stem Cells From Adipose Tissue. (8th March 2016) - Pachón-Peña, Gisela; Serena, Carolina; Ejarque, Miriam; Petriz, Jordi; Duran, Xevi; Oliva-Olivera, W.; Simó, Rafael; Tinahones, Francisco J.; Fernández-Veledo, Sonia; Vendrell, Joan
Abstract : Human adipose-derived stem cells (hASCs) were obtained from subcutaneous adipose tissue of healthy, adult, female donors (lean and obese) undergoing abdominal plastic surgery. The differences observed in proliferation, migration, and differentiation capacity in obese hASCs, compared with those of lean donors, at two different oxygen conditions, occurred in parallel with changes in cell surface markers, both under basal conditions and during differentiation. Obesity appears to be an important determinant of stem cell function independent of oxygen tension. Abstract: : Adipose tissue is a major source of mesenchymal stem cells (MSCs), which possess a variety of properties that make them ideal candidates for regenerative and immunomodulatory therapies. Here, we compared the immunophenotypic profile of human adipose-derived stem cells (hASCs) from lean and obese individuals, and explored its relationship with the apparent altered plasticity of hASCs. We also hypothesized that persistent hypoxia treatment of cultured hASCs may be necessary but not sufficient to drive significant changes in mature adipocytes. hASCs were obtained from subcutaneous adipose tissue of healthy, adult, female donors undergoing abdominal plastic surgery: lean ( n = 8; body mass index [BMI]: 23 ± 1 kg/m 2 ) and obese ( n = 8; BMI: 35 ± 5 kg/m 2 ). Cell surface marker expression, proliferation and migration capacity, and adipogenic differentiation potential of cultured hASCs at two different oxygen conditions were studied. Compared with lean-derived hASCs, obese-derived hASCs demonstrated increased proliferation and migration capacity but decreased lipid droplet accumulation, correlating with a higher expression of human leukocyte antigen (HLA)-II and cluster of differentiation (CD) 106 and lower expression of CD29. Of interest, adipogenic differentiation modified CD106, CD49b, HLA-ABC surface protein expression, which was dependent on the donor's BMI. Additionally, low oxygen tension increased proliferation and migration of lean but not obese hASCs, which correlated with an altered CD36 and CD49b immunophenotypic profile. In summary, the differences observed in proliferation, migration, and differentiation capacity in obese hASCs occurred in parallel with changes in cell surface markers, both under basal conditions and during differentiation. Therefore, obesity is an important determinant of stem cell function independent of oxygen tension. Significance: The obesity-related hypoxic environment may have latent effects on human adipose tissue-derived mesenchymal stem cells (hASCs) with potential consequences in mature cells. This study explores the immunophenotypic profile of hASCs obtained from lean and obese individuals and its potential relationship with the altered plasticity of hASCs observed in obesity. In this context, an altered pattern of cell surface marker expression in obese-derived hASCs in both undifferentiated and differentiated stages is demonstrated. Differences in proliferation, migration, and differentiation capacity of hASCs from obese adipose tissue correlated with alterations in cell surface expression. Remarkably, altered plasticity observed in obese-derived hASCs was maintained in the absence of hypoxia, suggesting that these cells might be obesity conditioned.